Early Modern Polish Hagiographic Works of the Capuchins and the Deficiencies in the Manuscript Collections of the Capuchin Province of Warsaw - Kapuścińska, Anna (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The Capuchins were brought to Poland in 1681 however Polish Capuchin friars had been activemuch earlier in pastoral working, also in the field of hagiography in other European countries: Italy,Switzerland, and Czech. We have our native textual traces that have survived from Renaissance and Baroquedocuments of the beatification and canonization processes of Capuchin Blessed and Saints as wellas their hagiographic biographies. Here we can mention eminent Polish friars, authors of ecclesiasticaltestimonies and vitae: Jan Baptista Fromberger, Grzegorz Stanisław, Franciszek Wacław Rozdrażewski.We can also be sure that in the Capuchin Order, parenetic significance of a saint’s life was especially appreciated.It is difficult to doubt that in Poland, where the hagiographical tradition had been rich anddistinguished, there was a strong emphasis on pastoral activity by means of vitae sanctorum. Unfortunatelywhen saying about the hagiographic works of the Capuchins in early modern Poland, particularlyin the present Province of Warsaw, we encounter some very serious problems; the complete lack of textssurviving from that time is the most severe one. The Russian partition of Poland and the Second WorldWar resulted in huge deficiencies in Capuchin book resources. Especially the German suppression of theWarsaw Uprising led to the destruction of libraries where unique manuscript collections were stored. Theonly method to say something about the early modern Polish Capuchin hagiography is to reconstructits character and scope on the basis of pre-war library catalogues and 19th century reprints of single texts.Thus we are able to confirm only four names of Capuchin hagiographic authors: Stanisław Ignacy Filipecki,Ludwik Wojciech Zaleski, Modest Jan Freindsteter and the most eminent and outstanding WiatorPiotrowski. We can be sure that their hagiographies focused specifically on Capuchin saints. We can alsodeduce that texts generally realized a narrative scheme vita – virtutes – miracula. That scheme, typicalfor beatification and canonization elite hagiography, had been carried out shortly after the Trent Counciland subsequently used in hagiological documentary writings from the 17th to the 19th century. Survivingreprints of two Piotrowski’s texts suggest that early Capuchin authors included ascetic-mystical and moraltheological content into their vitae and took care about a parenetic orientation of discourse and its correspondencewith contemporaneity. In the Library of the Capuchin Province of Warsaw in Zakroczymwe can also find some traces of later reception of missing manuscripts that confirm the practical natureof early modern Capuchin hagiographies.